Analisis penerapan penentuan harga jual menggunakan metode cost plus pricing dengan pendekatan full costing pada Kopi Chuseyo Manado - Rembet, Pingkan Christy; Budiarso, Novi S.; Korompis, Claudia W. M. (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to analyze the application of the cost plus pricing method using the full costing approach in determining the selling price at Kopi Chuseyo Manado. The background of the study is based on the franchise policy where the selling price is set centrally, without fully considering the local branch’s production and nonproduction costs. This research uses a descriptive qualitative method with a case study approach. Data were collected through interviews and documentation, then analyzed by calculating the cost of goods manufactured using the full costing method and determining the selling price by adding a profit margin. The results show a discrepancy between the centrally determined selling price and the price calculated using the cost plus pricing method. This method is considered more accurate as it includes all relevant costs, helping the business achieve optimal profit and avoid losses due to inaccurate pricing. The study recommends this method for similar MSMEs to improve pricing accuracy.